Blathmac i jego "Poemat" poświęcony Dziewicy Maryi - Szewczyk, Anna (Vox Patrum, 2004)
The author presents the poem on the Virgin Mary, the oldest in Ireland and one of the oldest in the Early Medieval Europe. This poem wrote Irish monk of the monastery on Iona, Blathmac (+ 825). The author presents biography of Blathmac and the most important aspects of theology of Mary (Mary companion in suffering, Virgin Mary, Mother Mary, Theotocos, Intercessor). The poem includes many names of Mary: Sancta, Dear, Beautiful, Queen, Bright, Brightneck, True Virgin, Sun of the women, Sun of the human race.